2017
DOI: 10.1080/09593330.2017.1388851
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment on microbial and heavy metal concentration in Clarias gariepinus (African catfish) cultured in treated wastewater pond in Kumasi, Ghana

Abstract: This study assesses the microbial and heavy metal distribution in African catfish (Clarias gariepinus) cultured in waste stabilization pond, and their subsequent suitability for human consumption. Treated wastewater-fed pond (WFP) was used in the culture of the fish with a non-wastewater fed pond (NWFP), fed with ground and rain water as control. Pond water, sediments and fish tissue (gill, liver, gut and skin) samples from both sources were analyzed for pathogens and heavy metal levels. Escherichia coli popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Besides these benefits, a number of drawbacks are associated with the use of wastewater for crop irrigation [ 4 , 10 , 12 ]. Wastewater contains potentially toxic elements (PTEs) such as zinc, chromium, copper, cadmium, nickel, lead, mercury, and parasitic worms, which can induce severe risks to the human health and the environment [ 13 , 14 , 15 ]. The use of untreated wastewater for crop irrigation can also cause soil hardening and shallow groundwater contamination [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these benefits, a number of drawbacks are associated with the use of wastewater for crop irrigation [ 4 , 10 , 12 ]. Wastewater contains potentially toxic elements (PTEs) such as zinc, chromium, copper, cadmium, nickel, lead, mercury, and parasitic worms, which can induce severe risks to the human health and the environment [ 13 , 14 , 15 ]. The use of untreated wastewater for crop irrigation can also cause soil hardening and shallow groundwater contamination [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the reported cases, the levels of pathogenic bacteria on the skin were within the acceptable or marginally acceptable limits, except for two studies, as reported by Harnisz and Tucholski and Mark et al 68,69 The microbial flora of fish tissues naturally originates from the water since fish passively accumulate microbial pathogens mostly on their skin and in their gut. 20,70 25,71 The results of this study also indicated that when the concentrations of faecal coliforms in the water were about 10 3 per 100 ml, they were not detected in the muscle or in most of the tested organs.…”
Section: Microbial Contamination In Tww and Cultured Fishmentioning
confidence: 84%
“…A study by Mark et al (2019), found that fish of the species Clarias gariepinus cultivated in ponds with domestic reclaimed water can have Fe and Cd levels within the maximum levels allowed by the FAO, WHO, and NOAA. The tissues that presented a higher bioaccumulation of toxic metals were the gills and liver with concentrations of 0.1 -2.0 mg kg −1 , which were still below the safety threshold for human consumption (1 -2 mg kg −1 ).…”
Section: Use Of Wastewater In Aquaculturementioning
confidence: 99%